AI-Driven Cloud Governance 2.0: Balancing Agility, Compliance, and Operational Efficiency in Hybrid Multi-Cloud Environments (International Journal of Engineering & Extended Technologies Research (IJEETR), 2024)
The paper discusses the way AI-informed cloud governance can enable organisations to control hybrid multi-clouds setting without a disruption in the balance between agility, compliance, and operational efficiency. The paper explains the way AI will aid in policy enforcement, resources control, security surveillance, and automate workloads. The results indicate that AI will cut on manual work, improve the accuracy of the decisions, and develop faster response to risks and performance issues. Resulting challenges also indicate, however, poor quality of data, skills deficiency, and inconsistency in policy implementation. It echoes the findings of the paper that AI-Driven Cloud Governance 2.0 can prove to be a potent asset provided with vivid frameworks, dependable data and ongoing organisational orientation
Keywords: Multi-Cloud; Cloud Governance; Hybrid; Agility; Operations; Compliance; AI